Oxygen-supplying ROS-responsive prodrug for synergistic chemotherapy and photodynamic therapy of colon cancer - Hao, Ying; Liu, Tailuo; Zhou, Hao; Xu, Runhao; Li, Ka; Chen, Mao; Chen, Yuwen (Frontiers in Pharmacology, 2024)
The synergistic treatment of chemotherapy and photodynamic therapy (PDT) has remarkable potential in cancer therapy. However, challenges remain, such as unstable chemotherapeutic drug release, suboptimal targeting, and reduced efficacy of PDT under hypoxic conditions commonly found in solid tumors. To address these issues, we use camptothecin (CPT) and pheophorbide a (Pa) incorporated through the functional thioketal which serves as the reactive oxygen species (ROS)-responsive trigger to construct a ROS-responsive prodrug (CPT-TK-Pa), then co-loaded with platinum nanozyme (PtNP) in distearylphosphatidylethanolamine-polyethylene glycol (DSPE-PEG) to obtain the ROS-responsive prodrug nanoparticle (CPT-TK-Pa/Pt NP). Specifically, the incorporated PtNP within CPT-TK-Pa/Pt NP positively catalyzes the conversion of hydrogen peroxide (H2O2) to oxygen, thereby ameliorating the hypoxic state of the tumor. This enhanced oxygen generation could replenish the oxygen that is consumed by Pa during 660 nm exposure, enabling controlled CPT release and amplifying the photodynamic response. In vitro investigations reveal the potency of CPT-TK-Pa/Pt NPs in inhibiting colon tumor cells. Given its ROS-responsive release mechanism and enhancement of PDT efficacy, CPT-TK-Pa/Pt NP has the potential to be a promising candidate for cancer therapy.